2012
DOI: 10.1097/mlr.0b013e318244d345
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use and Expenditures Associated With Access to the Medical Home for Children and Youth

Abstract: The medical home is associated with several domains of health service use, yet there is no evidence for its association with health care expenditures for children and youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 28 publications
3
26
3
1
Order By: Relevance
“…Although overall ED use in our study population was slightly higher than that found in other nationally representative samples of children, it was in the same range. 25,26 Future work is needed to assess the potentially variable effects of enhanced access on non-urgent ED use in general populations and in populations that have higher ED use, such as children with special health care needs and publicly insured children. Our finding of decreased ED use with extended hours for publicly insured children but not for CSHCN suggests that enhanced access alone may not address the complex needs of CHSCN but could mitigate barriers for low-income families with generally well children.…”
Section: Discussionmentioning
confidence: 99%
“…Although overall ED use in our study population was slightly higher than that found in other nationally representative samples of children, it was in the same range. 25,26 Future work is needed to assess the potentially variable effects of enhanced access on non-urgent ED use in general populations and in populations that have higher ED use, such as children with special health care needs and publicly insured children. Our finding of decreased ED use with extended hours for publicly insured children but not for CSHCN suggests that enhanced access alone may not address the complex needs of CHSCN but could mitigate barriers for low-income families with generally well children.…”
Section: Discussionmentioning
confidence: 99%
“…Although their results appear to conflict with our findings that costs were not a reason for unmet need among CSHCN lacking a medical home, the two studies address different concepts: Our work concerns parents’ perceptions of why they chose not to obtain needed health services for their children, while Porterfield and DeRigne analyzed reported out-of-pocket expenditures on health services for those who did obtain those services. In the general pediatric population, Romaire et al found that higher expenditures for prescription medications, outpatient and dental care were offset by lower expenditures for other types of care, with the result that total expenditures were the same for children with medical homes and those without [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Medical homes are associated with less unmet need among CSHCN, among children with disabilities [20-24] , and among U.S. children generally [25]. Lacking such help, the families of CSHCN without medical homes may have problems identifying health care providers who meet their child's needs and coordinating services among multiple providers, contributing to their unmet needs for care.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Importantly, studies suggest that if savings do emerge, they are likely to come from reductions in emergency department visits or hospitalizations 23,25 and thus will not financially benefit primary care practices un- less financial incentives or risk-based payment models are in place. However, our participants acknowledged that several of the newly implemented activities were critical to improving care quality and were thankful that the application process drove their organizations to understand the need to dedicate time and resources to make these advancements.…”
Section: Discussionmentioning
confidence: 99%